The status of invasive plants and animals in Cu Lao Cham biosphere reserve, Quang Nam province, Vietnam - Tai, Vu Anh; Khanh, Uong Dinh; Anh, Luu The; Thu Hien, Le Thi (Academia Journal of Biology, 2018)
The biodiversity of Cu Lao Cham Biosphere Reserve (Hoi An City, Quang Nam Province) has been faced with some passive impacts, one of which is invasion/expansion of alien species. In 2017, according to the data of GISD, CABI and the Inter-ministerial Circular No.27/2013/TTLT-BTNMT-BNNPTNT, based on filed survey conducted in May, 19 alien plant and 3 alien animal species were recorded in the biosphere reserve. Among them, 13 plant species were identified as invaders, of which details were assessed in this study; among those invader plants, 3 species were ranked at medium risk and the 10 others were ranked at low risk. All of the medium risk-invasive plant species have been appeared on the islands but one of them - siam weed (Chromolaena odorata) were not identified as impacting to the mainland of the biosphere reserve. Likewise, all of the alien animal species have been not recognized as the invasive species. In general, the impact of alien species found in the Cu Lao Cham was assessed as “Low Risk”. The impact status of invasive species in the Hoi An mainland part is more serious than the situation in the islands. Base on the results, we suggest that, five species, beggar-ticks (Bidens pilosa), coast morning glory (Ipomoea cairica) Bay Biscayne creeping-oxeye (Sphagneticola trilobata), Blue porterweed (Stachytarpheta jamaicensis) and billygoat-weed (Ageratum conyzoides) should be added in the invasive appendix of the national invasive species list while three other species as vilfa stellata (Cynodon dactylon), guava (Psidium guava) and rose myrtle (Rhodomyrtus tomentosa) should be listed in the potential appendix of that list. It is necessary to conduct some survey to obtain solution to control invasive species as soon as possible to protect the biodiversity of this study area. Citation: Vu Anh Tai, Uong Dinh Khanh, Luu The Anh, Le Thi Thu Hien, 2017. The status of invasive plants and animals in Cu Lao Cham biosphere reserve, Quang Nam province, Vietnam. Tap chi Sinh hoc, 39(4): 434-450. DOI: 10.15625/0866-7160/v39n4.10082. *Corresponding author: tai.botany@gmail.com Received 15 June 2017, accepted 12 December 2017